Implementing the technology shift from 2D to 3D: insights and suggestions for umpire educators - Kaiser, Keone; Walters, Simon; Sheehy, Kevin; Murray, Eoin; Spencer, Kirsten (Frontiers in Virtual Reality, 2024)
Effective methods to improve decision-making in sports officiating particularly with the current and ongoing issues with in-person training, means new methods of remote training must be developed. Traditional training officials occurs as primarily 'in-person coaching' at matches, with supporting training manuals and 2D broadcast analysis. However, live matches present difficulties in implementation, while manuals and 2D broadcast videos may not sufficiently ensure learning transfers to real situations. Due to its ease of use, first-person perspective and the ability to analyse live and post-event remotely, 360° virtual reality video technology (360°VR) offers an alternative technological solution for developing decisionmaking accuracy for sports officials across multiple sports.This study sought to assess the ecological validity (EV) of using 360°VR technology to enable remote teaching of decision-making. Decision-making quality and accuracy in softball umpires were similar when using 360°VR and traditional method (2D broadcast footage), but 360°VR received significantly higher EV values than the 2D Broadcast videos.In addition, interviewed participants expressed excitement about using 360°VR to augment traditional umpiring manual and rulebooks. The results show that 360°VR has the potential to enhance or replace traditional remote learning methods for decision-making in softball umpires and allow softball learning to reach a much wider umpire audience